2020
DOI: 10.1007/s00426-020-01338-9
|View full text |Cite
|
Sign up to set email alerts
|

Functions of spontaneous and voluntary future thinking: evidence from subjective ratings

Abstract: Future thinking is defined as the ability to withdraw from reality and mentally project oneself into the future. The primary aim of the present study was to examine whether functions of future thoughts differed depending on their mode of elicitation (spontaneous or voluntary) and an attribute of goal-relatedness (selected-goal-related or selected-goal-unrelated). After producing spontaneous and voluntary future thoughts in a laboratory paradigm, participants provided ratings on four proposed functions of futur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 79 publications
(178 reference statements)
1
9
0
Order By: Relevance
“…These functions share the common feature of being task or goal-oriented, and in the service of giving rise to related, purposeful action. This is perhaps unsurprising given that a primary role of imagining the future is to address current concerns (Barsics et al, 2016;Cole & Berntsen, 2016), and that even mind-wandering has been found to frequently involve autobiographical planning (Baird, Smallwood, & Schooler, 2011;Duffy & Cole, 2020). These findings are also consistent with a previous diary study where the participants nominated 'planning actions' and 'intention-formation' as the most frequent reasons for thinking about the future (Barsics et al, 2016).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…These functions share the common feature of being task or goal-oriented, and in the service of giving rise to related, purposeful action. This is perhaps unsurprising given that a primary role of imagining the future is to address current concerns (Barsics et al, 2016;Cole & Berntsen, 2016), and that even mind-wandering has been found to frequently involve autobiographical planning (Baird, Smallwood, & Schooler, 2011;Duffy & Cole, 2020). These findings are also consistent with a previous diary study where the participants nominated 'planning actions' and 'intention-formation' as the most frequent reasons for thinking about the future (Barsics et al, 2016).…”
Section: Discussionsupporting
confidence: 82%
“…Some researchers have adopted this level of analysis through explicitly asking individuals the purpose of future thinking, and providing a limited set of options (Barsics et al, 2016;D'Argembeau et al, 2011). In other studies people are asked to imagine a series of future events and to evaluate their perceived functions using rating scales (Duffy & Cole, 2020;Özbek, Bohn, & Berntsen, 2018;Rasmussen & Berntsen, 2013). To date, however, no standardized tool has been evaluated to assess individual variation in why people engage in future thinking.…”
mentioning
confidence: 99%
“…We call on other researchers to explore different functions, and specifically compare functions of voluntary and spontaneous future thought in single studies. We note the current dearth of such research (although see Duffy & Cole, 2019). But in this position paper, our focus remains on the relevance of spontaneous future thinking to goal-oriented cognition and behaviour, which coheres with several well-established theoretical accounts (e.g., Klinger, 2013, see below).…”
Section: Spontaneous Future Thinkingmentioning
confidence: 53%
“…Although deliberate (instructed) generation of standardized imagery scenes may allow a more controlled investigation of the impact of imagery generation on factors such as mood (e.g., ), decision-making (e.g., Gaesser & Schacter, 2014), or behaviour (e.g., Pictet et al, 2011Renner et al, 2019), we need to be cautious about extrapolating from this to involuntary, spontaneously occurring imagery, particularly as there is some evidence that involuntary mental imagery may differ in its emotional impact and other phenomenological characteristics compared to its voluntarily generated counterparts (e.g., Barsics et al, 2016;Berntsen & Hall, 2004;Cole et al, 2016), and this is a matter of ongoing debate (e.g., Barzykowski et al, 2019;Barzykowski & Niedźwieńska, 2018;Barzykowski & Staugaard, 2016Schlagman & Kvavilashvili, 2008). In fact aside from participants' subjective reports (e.g., Barsics et al, 2016;D'Argembeau et al, 2011;Duffy & Cole, 2020;Rasmussen & Berntsen, 2013) we have very little, if any, direct evidence as to the functions and impact PREPRINT OF UNPUBLISHED MANUSCRIPT: see https://osf.io/whk2b/ v4.0 02. 07.20 of what seems to be one of the most commonly-experienced forms of mental imagery.…”
Section: Inducing Positive Involuntary Mental Imagery In Everyday Lifmentioning
confidence: 99%